Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages milk contains about 12 grams of milk protein. The only possible source of this protein is the protein in the mother's diet. The human body is not a perfect biochemical factory and cannot give an output in the milk of one gram of protein for each gram eaten. The woman requires about 24 grams of protein, of good quality, in her diet to give out 12 grams in her milk. This amount of 24 grams is over and above what she requires for the maintenance of her own body. But the poorer women, those who can only spend four or five shillings per head per week on food, do not get anything like an adequate maintenance ration of protein, let alone additional quantities for milk production, so there is little wonder that she can spare none for milk. Would it not be better to feed the woman properly so that she could feed her infant, than to pay out money from the rates to bottle-feed the infants? Education authorities spend large sums of money on dentistry for school children; why not feed the children properly so that the need for dentistry would largely disappear? Is it not better to prevent sickness and incapacity than to pay for medical treatment, sickness benefit, etc? Our system of social economics is profoundly unsatisfactory. The remedy? That is for our people to determine. If the public is sufficiently cognisant of the true facts, and the public conscience sufficiently moved by the evil of the under-nourishment and the mal-nourishment of the poorer classes of the community, and is convinced that the evils attendant upon these conditions are preventable, then they will be prevented. A boldly designed and courageously carried out National Food Policy must form the main line of attack upon the evil of poverty. The producer of agricultural and dairy 13 15X/2/217/2